2014
DOI: 10.1002/jez.1864
|View full text |Cite
|
Sign up to set email alerts
|

Growth and wear of incisor and cheek teeth in domestic rabbits (Oryctolagus cuniculus) fed diets of different abrasiveness

Abstract: Although patterns of tooth wear are crucial in palaeo-reconstructions, and dental wear abnormalities are important in veterinary medicine, experimental investigations on the relationship between diet abrasiveness and tooth wear are rare. Here, we investigated the effect of four different pelleted diets of increasing abrasiveness (due to both internal [phytoliths] and external abrasives [sand]) or whole grass hay fed for 2 weeks each in random order to 16 rabbits (Oryctolagus cuniculus) on incisor and premolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
114
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 83 publications
13
114
1
Order By: Relevance
“…In a previous study, we demonstrated a significant and positive relationship between tooth growth and wear of incisor and cheek teeth in rabbits (Müller et al., ), dispelling the concept of constant growth rates but suggesting a feedback mechanism between tooth growth and wear that adapts to dietary influences. These findings were similar to previous findings where incisor growth and wear rates of rabbits, guinea pigs and other rodents varied on different diets (Wolf and Kamphues, , ).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In a previous study, we demonstrated a significant and positive relationship between tooth growth and wear of incisor and cheek teeth in rabbits (Müller et al., ), dispelling the concept of constant growth rates but suggesting a feedback mechanism between tooth growth and wear that adapts to dietary influences. These findings were similar to previous findings where incisor growth and wear rates of rabbits, guinea pigs and other rodents varied on different diets (Wolf and Kamphues, , ).…”
Section: Introductionmentioning
confidence: 56%
“…These findings were similar to previous findings where incisor growth and wear rates of rabbits, guinea pigs and other rodents varied on different diets (Wolf and Kamphues, , ). With respect to a current debate (Mainland, ; Sanson et al., ; Damuth and Janis, ; Lucas et al., ) whether herbivore teeth are only affected by external abrasives (dust, grit) or also by internal abrasives (phytoliths), we found that rabbit teeth also experienced different levels of wear in relation to concentrations of dietary internal abrasives (Müller et al., ).…”
Section: Introductionmentioning
confidence: 66%
“…The mean number of polishing striations left after chewing shows that the grass and lucerne diets caused less, and the grass-rice-sand diet more overwriting than the most phytolith-containing grass-rice diet. Rabbit and guinea pig studies with the same diets [11,12] also showed that absolute wear rate increased from lucerne to grass to grass-rice and to grass-rice-sand. This was also evident in our CT scan data.…”
Section: Discussionmentioning
confidence: 89%
“…Low silica content in the diet also resulted in more variable surface textures and microwear patterns. Exposing rabbits and guinea pigs (Cavia porcellus) to diets designed to reflect different proportions of internal and external abrasives (sand), and measuring the resulting effects manually and by computed tomography, differences in wear and in the responding tooth growth could be demonstrated [11,12]. Most recently, the effects of external grit on the microwear signature were demonstrated in live sheep [13] and angles of approach in chewing were shown to affect microwear [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely, as clinical signs in guinea pigs are often overlooked by owners [24]. Guinea pigs were also not physically examined by the experimenter, as was performed in previous studies [21,34,35]. Additionally, as dental disease can be difficult to diagnose due to guinea pigs typically having a small mouth opening and a long narrow oral cavity, the true prevalence is often underestimated even with a clinical examination [5].…”
Section: Discussionmentioning
confidence: 99%